Strength Analysis for 70% Low-floor Tram Car Motor Bogie Frame - LI Jincheng; Li Fu; Yang Yang (机车电传动)
Basic parameters of the 70% low-floor tram car and structural features of the motor bogie were introduced. The calculation outline of motor bogie frame of the 70% low-floor tram car was made based on the European standard EN13749. The finite element analysis software ANSYS was used to calculate the static strength, fatigue strength and modal analysis of the motor bogie frame. The results showed that the frame was able to meet the strength requirements, each-order modal model of which was on relatively high frequency, without obviously weak part.